Implementasi Asas Kebebasan Berkontrak dan Pengaruhnya Terhadap Kegagalan Pekerjaan Konstruksi - Agustina (Jurnal Ilmu Sosial dan Humaniora, 2023)
This study aims to comprehensively discuss the implementation of the principle of freedom of contract in construction work contracts, and examine the legal consequences of unequal work contracts in construction work. This type of research is normative in nature with a descriptive-analytical approach to studying existing legal symptoms and problems and testing them based on statutory regulations and legal norms. The results of this study indicate that the principle of freedom of contract in construction work contracts cannot be fully implemented, due to the use of standard clauses in the preparation of contracts. An unbalanced work contract can have legal consequences for the interests of the parties resulting in a dispute arising, so that the contract can be canceled or declared null and void.